Pengaruh Harga Produk, Customer Review Dan Preferensi Pengalaman Pembelian Terhadap Keputusan Pembelian Mahasiswa Manajemen Upgris Pada Shopee Dan TikTok Shop - Welly Dhea Ayu Hapsari; Rizky Fatkhur Rohman; Yunia Nur Anisa; Rauly Sijabat (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze the influence of product prices and customer reviews on purchasing decisions of Management students at PGRI University Semarang (Upgris) on the e-commerce platforms Shopee and TikTok Shop. In the current digital era, e-commerce has become one of the main channels for consumers to make purchases. Two important factors that consumers often consider before making a purchase are product price and customer reviews. The research method used is quantitative with a survey approach. Data was collected through a questionnaire distributed to 36 Upgris Management students who actively use Shopee and TikTok Shop.The research results show that both product price and customer reviews have a significant influence on purchasing decisions. Specifically, product price has a greater influence than customer reviews in determining purchasing decisions on both platforms. Apart from that, there is a difference in the level of trust in customer reviews on Shopee and TikTok Shop, where students tend to trust reviews on Shopee more. It is hoped that these findings will provide insight for e-commerce businesses in designing effective marketing strategies by considering price factors and customer reviews.